South African Open Distance Elearning Student: The Types, Effectiveness, and Preference of Feedback Support - Morakinyo Akintolu; Mohamed Ahmed Mitwally; Moeketsi Letseka (West African Journal of Open and Flexible Learning)
Historically feedback is perceived as a unidirectional flow of information from e-tutor to student, however, the feedback mechanisms ecology highlights the significance of establishing links between students and lecturers, as well as students and institutions. This study examines the various types of feedback, their efficacy, and the preferences of students in the context of Open Distance eLearning (ODeL). The study explores the feedback preferences of Open Distance eLearning (ODeL) students in South Africa using a quantitative research methodology. The study included 3842 participants who responded to an online survey. The findings indicate that proactive and prompt feedback significantly enhances student learning, emphasising the need for constructive comments within the ODeL framework. The study also identifies specific feedback forms requested by students to improve their educational experience. The findings suggest that effective feedback mechanisms are crucial in ODeL environments, providing actionable insights for educators to optimise their feedback strategies.